Determination of thresholds for storm impacts - Ferreira, Óscar (2018)
Storms are responsible for important erosion, coastal retreat and damage when infrastructures are placed within their acting area. The characterisation of storm parameters and associated thresholds for erosion and damage are therefore of fundamental importance for coastal management purposes. This work presents ways of determining thresholds for important morphological changes (including erosion), overwash occurrence and damage associate to storm occurrence. These methods were tested and applied to Ancão Peninsula (South Portugal) and the results shown. The use of these approaches will enable coastal managers to have a quantitative knowledge of consequences associated to each particular storm and to act accordingly, for instance defining set-back lines, designing nourishments or implementing evacuation plans.